2020
DOI: 10.1007/s10143-020-01377-1
|View full text |Cite
|
Sign up to set email alerts
|

Revision by S2-alar-iliac instrumentation reduces caudal screw loosening while improving sacroiliac joint pain—a group comparison study

Abstract: Lumbosacral instrumentation continues to be challenging due to complex biomechanical force distributions and poor sacral bone quality. Various techniques have therefore been established. The aim of this study was to investigate the outcome of patients treated with S2-alar-iliac (S2AI), S2-alar (S2A), and iliac (I) instrumentation as the most caudal level. Sixty patients underwent one of the 3 techniques between January 2012 and June 2017 (S2AI 18 patients, S2A 20 patients, I 22 patients). Mean age was 70.4 ± 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Highly statistically significant (p-value < 0.001) decreased postoperative ODI (31. 7 This table shows the description of follow up days in all studied patients. The mean follow up days of all studied patients was 8.2 ± 3.2 days with minimum follow up days of 6 days and maximum follow up days of 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Highly statistically significant (p-value < 0.001) decreased postoperative ODI (31. 7 This table shows the description of follow up days in all studied patients. The mean follow up days of all studied patients was 8.2 ± 3.2 days with minimum follow up days of 6 days and maximum follow up days of 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have con rmed the advantages of S2AI technology, Researchers such as Elder et al [10] have found that both methods of pelvic xation were effective in relieving preoperative pain and dysfunction, and there was no signi cant difference in the probability of L5-S1 pseudoarthrosis and sacroiliac joint pain between the two xation methods, but compared with IS technique, the application of S2AI screw can signi cantly reduce the risk of incision infection, dehiscence, symptomatic screw protrusion, and reoperation. And Krieg et al [11] argue that the S2AI screw had a lower rate of sacroiliac joint pain and the possibility of screw loosening than IS in thoracolumbar surgery of the same length. This is also consistent with the results of a META analysis from 5 retrospective studies by Garza et al [12] .…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved 672 articles, of which 14 met the inclusion criteria [2,[8][9][10][11][12][13][14][16][17][18][19][20][21]. Three studies focused on S2AI [11,13,21], six on IS [8][9][10]12,14,18], and five on S2AI and IS [2,16,17,19,20].…”
Section: Paper Selection and Characteristicsmentioning
confidence: 99%
“…We retrieved 672 articles, of which 14 met the inclusion criteria [2,[8][9][10][11][12][13][14][16][17][18][19][20][21]. Three studies focused on S2AI [11,13,21], six on IS [8][9][10]12,14,18], and five on S2AI and IS [2,16,17,19,20]. The flow chart in Fig.…”
Section: Paper Selection and Characteristicsmentioning
confidence: 99%